Deciphering the Complex Relationship between AEWA's and the Bonn Convention's Respective Exemptions to the Prohibition of Taking. Issue 3 (3rd July 2019) - Lewis, Melissa
Abstract: This article explores several interpretive complexities associated with Article III(2)(a) of the Agreement on the Conservation of African-Eurasian Migratory Waterbirds (AEWA). Article III(2)(a) attempts to avoid incongruity between AEWA and the Convention on the Conservation of Migratory Species of Wild Animals (CMS)—specifically, in relation to the Convention's prohibition on the taking of animals from certain species. However, an apparent misalignment between this provision and other aspects of AEWA's legal text results in various legal uncertainties regarding the grounds of exemption that AEWA parties may invoke to allow the taking of certain protected species, as well as the potential for further developing AEWA's exemptions regime in the future. The article investigates the interplay between relevant provisions of AEWA and the CMS, makes suggestions regarding the possible interpretations of these provisions, and identifies the practical implications of these interpretations.